Faktor Faktor yang Mempengaruhi Pendapatan UMKM Pengguna Layanan Online Food Delivery di Kota Bandar Lampung - Triyono, Triyono; Marga Saty, Fadila; Budi Trisnanto, Teguh; Berliana, Dayang (Journal of Food System & Agribusiness, 2024)
During the post-pandemic period, many MSMEs in Bandar Lampung still use online food delivery services, because these services are a way for sellers to increase revenue. Consumer behavior has also begun to take its shape since the Covid-19 pandemic, namely shopping habits through online media. Therefore, further research is needed related to the analysis of factors affecting the income of culinary MSMEs using online food delivery services in Bandar Lampung City, to see how it would develop in the post-pandemic period. This research was conducted at 58 culinary MSME outlets, namely meatballs and geprek chicken in Bandar Lampung, which employ online food delivery services (GoFood) with a minimum criteria of 4.3 star rating. The data analysis methods used in this study are descriptive analysis method, income analysis, and multiple linear regression analysis. The results showed that the factors that have the most influence on the income of culinary MSMEs using online food delivery services are price and number of orders.